2022
DOI: 10.3390/ijerph19105953
|View full text |Cite
|
Sign up to set email alerts
|

EEG Global Coherence in Scholar ADHD Children during Visual Object Processing

Abstract: Among neurodevelopmental disorders, attention deficit hyperactivity disorder (ADHD) is the main cause of school failure in children. Notably, visuospatial dysfunction has also been emphasized as a leading cause of low cognitive performance in children with ADHD. Consequently, the present study aimed to identify ADHD-related changes in electroencephalography (EEG) characteristics, associated with visual object processing in school-aged children. We performed Multichannel EEG recordings in 16-year-old children u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It is reasonable that these alterations have repercussions on brain activity, which can be registered via electroencephalography in areas like the frontal lobe. Different studies have already demonstrated deficits in neuropsychological mechanisms like spatial organization and behavioral modulation in subjects with ADHD [58]. So, it would be interesting to compare genetic findings to neurophysiological data to obtain a progressively more complete profile of ADHD necessary for a tailored therapy according to the rules of precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable that these alterations have repercussions on brain activity, which can be registered via electroencephalography in areas like the frontal lobe. Different studies have already demonstrated deficits in neuropsychological mechanisms like spatial organization and behavioral modulation in subjects with ADHD [58]. So, it would be interesting to compare genetic findings to neurophysiological data to obtain a progressively more complete profile of ADHD necessary for a tailored therapy according to the rules of precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…These features were then reduced using a genetic algorithm, and then the chosen features were used to learn an ANN. Elsewhere, the study [ 27 ] explored the relationship between ADHD and visuospatial problems, which involve challenges in processing visual information. This study examined 16-year-old adolescents with ADHD and analyzed their brain activity using EEG during a visual processing task, comparing it to a control group.…”
Section: Related Workmentioning
confidence: 99%
“…EEG data can monitor alterations in brain function caused by ADHD [ 25 , 26 ]. However, complex-level structures in the complex records generated by the brains of humans are challenging to identify [ 27 ]. With the help of machine learning (ML), detecting these complicated patterns is achievable.…”
Section: Introductionmentioning
confidence: 99%